EKSISTENSI TARI PIRIANG HOYAK INDANG BADANTIANG DI SANGGAR SHIMPHONY BADANTIANG KAMPUNG MUARO KECAMATAN LUBUK BASUNG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the "Existence of Piriang Hoyak Indang Badantiang Dance at Shimphony Badantiang Studio in Muaro Village, Lubuk Basung District." This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself, assisted by writing tools and a camera. Data were collected through literature studies, observation, interviews and documentation. The steps to analyse the data are collecting data, describing the data and concluding the data. Research on the Existence of the Piriang Hoyak Indang Badantiang Dance at the Shimphony Badantiang Studio in Muaro Village, Lubuk Basung District, has developed very well and received excellent appreciation from the community, with the high interest of the public in this dance evident from the audience's enthusiasm at every performance, as well as the numerous requests for performances at various events. The active role of the Shimphony Badantiang Studio in coaching, training, and improving the quality of performances has been crucial in promoting the existence of the Piriang Hoyak Indang Badantiang Dance within the community.